Near-Peer Teaching and Exam Results: The Acceptability, Impact, and Assessment Outcomes of a Novel Biological Sciences Revision Programme Taught by Senior Medical Students. (27th November 2014) - Mann, Jake; Protty, Majd B.; Duffy, John; Mohammed, Mohammed; Wiskin, Connie
Abstract : Background . Near-peer teaching is becoming increasingly popular as a learning methodology. We report the development of a novel near-peer biological sciences revision course and its acceptability and impact on student confidence and exam performance. Methods . A cross-sectional analysis of tutee-completed evaluation forms before and after each session was performed, providing demographic details, quality scores, and self-rating of confidence in the topic taught on a 0 to 100 mm visual analogue scale (VAS). The confidence data was examined using analysis of means. Exam performance was examined by analysis of variance and canonical correlation analysis. Results . Thirty-eight sessions were delivered to an average of 69.9 (±27.1) years 1 and 2 medical students per session generating 2656 adequately completed forms. There was a mean VAS gain of 19.1 (5.3 to 27.3) in self-reported confidence. Looking at relationship between attendance and exam scores, only two topics showed significant association between number of sessions attended and exam performance, fewer than hypothesised. Conclusion . The present study demonstrates that near-peer teaching for biological sciences is feasible and is associated with improved self-reported confidence in the sessions taught. The outcome data, showing significant effect for only a small number of items, demonstrates the difficulty of outcome related research.